Sintesis Nanopartikel Perak Menggunakan Ekstrak Daun Kluwak Pangium edule Reinw Sebagai Bioreduktor dan Uji Aktivitasnya Sebagai Antioksidan - Indrawati Patabang; Syahruddin Kasim; Paulina Taba (Universitas Hasanuddin, 2019)
Silver nanoparticles have been synthesized using kluwak leaf extract (Pangium edule Reinw) as bioreductor and antioxidant activity assay. The nanoparticles formed were monitored by observing UV-Vis absorption and characterized by using FTIR, PSA, XRD and SEM instruments. The result of functional group characterization with FTIR show that the functional groups OH, C = O, C-O and CH2 act as Ag+ reducing agent. The size of silver nanoparticles was determined by using Particle Size Analyzer (PSA) and the result show average particle size distribution of 93.2 nm. Morphology of AgNp were observed by Scanning Electron Microscope (SEM) and X-Ray Difraction (XRD) analysis show result of 51,78 nm. The antioxidant activity was shown by in kluwak leaf extract and silver nanoparticles with IC50 values respectively 831,33 ppm dan 1493,09 ppm.